2012
DOI: 10.1089/hum.2011.201
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Zinc-Finger Proteins Can Compensate Genetic Haploinsufficiency by Transcriptional Activation of the Wild-Type Allele: Application to Willams-Beuren Syndrome and Supravalvular Aortic Stenosis

Abstract: Williams-Beuren syndrome (WBS) and supravalvular aortic stenosis (SVAS) are genetic syndromes marked by the propensity to develop severe vascular stenoses. Vascular lesions in both syndromes are caused by haploinsufficiency of the elastin gene. We used these distinct genetic syndromes as models to evaluate the feasibility of using engineered zinc-finger protein transcription factors (ZFPs) to achieve compensatory expression of haploinsufficient genes by inducing augmented expression from the remaining wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Because all patients with RBM20 mutations described to date are heterozygous (the other allele being functional), we reasoned that transcriptional upregulation of RBM20 would be beneficial. Similar approaches of gene expression upregulation in haploinsufficiency have been beneficial in disease models of Dravet syndrome ( Hsiao et al, 2016 ) and vascular stenosis ( Zhang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because all patients with RBM20 mutations described to date are heterozygous (the other allele being functional), we reasoned that transcriptional upregulation of RBM20 would be beneficial. Similar approaches of gene expression upregulation in haploinsufficiency have been beneficial in disease models of Dravet syndrome ( Hsiao et al, 2016 ) and vascular stenosis ( Zhang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger proteins are involved in the regulation of transcription or translation by specific binding of the target molecules. Different combined with DNA, RNA, DNA-RNA, protein, or zinc finger motifs, which result in zinc finger proteins present multifunctional in biological processes [49,50]. ZC3H13 is a classical CCCH zinc finger protein and the encoding gene is located in human chromosome 13q14.13 [51].…”
Section: Discussionmentioning
confidence: 99%
“…miR‐29 uniquely targets several genes that regulate ECM production and may influence disease pathologies associated with abnormal ECM production. Previous work has shown that anti‐miR‐29 can upregulate elastin mRNA and protein levels in two diseases of elastin haploinsufficiency, Williams–Beuren syndrome (WBS) and supraventricular aortic stenosis (Zhang et al , ). Chronic administration of LNA‐miR‐29 reduces aortic aneurysm formation in angiotensin II and Marfan syndrome models via upregulation of several ECM genes (Merk et al , ) providing in vivo evidence supporting the promise of miR‐29 antagonism reducing the extent of vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Using anti‐miRNAs (either cholesterol‐modified or locked nucleic acid analogs to base pair with endogenous miRNAs) to antagonize endogenous miRNA, we and others have successfully targeted miR‐29 in vivo and in vitro , and have consistently demonstrated increased ECM components to restore vessel dynamics without obvious off‐target effects. Interestingly, while several components of the ECM decrease in CVD, miR‐29 expression increases in the vasculature (van Rooij et al , ; Boon et al , ; Takahashi et al , ; Zhang et al , ,b; Yang et al , ; James et al , ; Han et al , ). Thus, we investigated whether the modulation of miR‐29 and its putative gene targets affects atheroma formation and composition, and might offer a new approach to promote favorable plaque remodeling.…”
Section: Introductionmentioning
confidence: 99%